1994
DOI: 10.1017/s0890037x00028815
|View full text |Cite
|
Sign up to set email alerts
|

Potential Regulatory Problems Associated with Atrazine, Cyanazine, and Alachlor in Surface Water Source Drinking Water

Abstract: Post-application seasonal (May-July) average concentrations of atrazine, cyanazine, and, to a lesser extent, alachlor sometimes exceed their Maximum Contaminant Levels (MCLs) (3 ug/L for atrazine and 2 ug/L for alachlor) or Maximum Contaminant Level Goal (MCLG) (1 ug/L for cyanazine) in surface waters of the Mississippi and Great Lakes Basins. These three chemicals are among the primary pre-emergent herbicides applied to corn. MCLs and MCLGs are compared to annual average concentrations for regulatory purposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Many studies have shown atrazine movement from the point of application in runoff water (see Nelson and Jones 1994, and references cited therein) (Table 4). Amounts detected for surface runoff studies range from < 0.1 010 to 7.20/0 of applied atrazine (Gaynor et al 1992.…”
Section: B Movement To Surface Watermentioning
confidence: 99%
“…Many studies have shown atrazine movement from the point of application in runoff water (see Nelson and Jones 1994, and references cited therein) (Table 4). Amounts detected for surface runoff studies range from < 0.1 010 to 7.20/0 of applied atrazine (Gaynor et al 1992.…”
Section: B Movement To Surface Watermentioning
confidence: 99%
“…Best management practices (BMPs) have been developed to reduce pesticide movement into nontarget areas and reduce contamination of water. BMP guidelines include conservation tillage, buffer strips and setbacks, crop rotation, between-row cultivation, herbicide incorporation, application timing, split applications, reduced rates, and alternative herbicides (Baker and Mickelson 1994;Devlin and Regehr 1996;Donald et al 2004;Nelson and Jones 1994;Wright et al 1993). Off-target movement is also influenced by the physical properties of the herbicides used.…”
Section: Introductionmentioning
confidence: 99%
“…New best management practices are needed to reduce offsite herbicide, nutrient, and sediment movement in runoff (Logan et al 1987;Logan 1993;Nelson and Jones 1994) and minimize herbicide contamination of surface and ground water (Fawcett 1998) without compromising farmers' economic or soil conservation goals. Moreover, if best management practices are to be adopted and used, they must be practical and acceptable to farmers (Rikoon et al 1996).…”
mentioning
confidence: 99%